DEVELOPMENT OF THE AGRARIAN SECTOR: TRANSFORMATION OF LOGISTICS LINKS AND ECONOMIC EFFICIENCY OF GRAIN ENTERPRISES - VASYLYNA, Orysia; POPADYNETS, Nazariy; YAKHNO, Tetyana; SADURA, Oksana; KRAVCHYK, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the strategic role of Ukraine’s agricultural sector in the context of modern globalization and intense international competition. It highlights the significance of grain production enterprises within the country’s agro-industrial complex, which play a key role in shaping both domestic and international grain markets. The study addresses the issue of economic efficiency of these enterprises. It is established that the development of effective management approaches and optimization mechanisms for agricultural enterprises will contribute to solving the problem of stabilizing operations and enhancing international competitiveness. The factors influencing the economic efficiency of grain production were examined, taking into account the research of leading scholars, which allowed the development of comprehensive recommendations for improving the conditions of agricultural business. Significant changes in the grain market caused by military actions and the political situation, which significantly reduced the sowing areas and disrupted traditional logistics of export through sea ports, are described. Before the aggression, the main share of grain was exported through Black Sea ports, specifically through Mykolayiv and Odesa, accounting for 95% of all grain shipments. Military actions led to the blockade of these routes, forcing a reorientation of grain export to western ports, resulting in significant logistical costs. The necessity of adapting logistical chains and finding alternative export routes to stabilize agricultural exports and minimize the impact on global food security is emphasized. Based on the analysis, ways to optimize the agricultural sector are proposed, including through state support for farmers, subsidized lending, provision of planting materials and fuel, and the need for demining and ensuring safe working conditions. The prospects for further research in the direction of innovative development of the agricultural sector to enhance its productivity and competitiveness are outlined.